Case Report: Decoding genetic risks of vascular parkinsonism: a case series - Shalash, Ali; El-Shafie, Salma; George, Peter; Roushdy, Tamer; Fathy, Mai; Yousef, Mohamed H.; El-Belkimy, Mahmoud; Abdulghani, Mohamed Ossama; Salama, Mohamed (Frontiers in Genetics, 2025)
BackgroundVascular parkinsonism (VaP) is a subtype of parkinsonism which needs better characterization of its risks and determinants.ObjectiveThe aim of this report is to present an understanding of genetic risks of vascular parkinsonism.MethodsFive participants diagnosed with VaP were recruited and Whole Exome Sequencing (WES) was performed to analyze deleterious variants in relevant genes associated with vascular and parkinsonian diseases.ResultsWe identified several candidate risk variants for VaP in our patients, particularly in LRRK2, PLA2G6, TGM6, BSN, UBR4, CD36 and NOTCH3, that are different from the classical Parkinson’s disease -associated variants.ConclusionIn this case series we highlighted the complexity of genetic contributions to VaP through predicted deleterious variants in genes associated with parkinsonism, cerebrovascular disease as well as collagen-related genes.